Sompa Tanah in Makassar Bugis Customary Marriages: Legal, Religious, and Cultural Perspectives - Maloko, M. Tahir; Indiyanto, Agus; Fernando, Henky; Larasati, Yuniar Galuh (Jurnal Ilmiah Peuradeun, 2024)
The submission of dowry in the form of land (Sompa Tanah), as practiced by the Bugis community in Bone, reflects the flexibility of local mechanisms in addressing real-world challenges based on the ideal values of tradition. This study is important in the broader discourse on dowry, which often highlights cultural legitimacy in perpetuating violence and the subordination of women. The provision of Sompa Tanah in Bugis society serves as a cultural, legal, and religious mechanism to establish legal certainty regarding rights and obligations in marital relations. This descriptive qualitative research draws on observation and interview data, which are then analyzed contextually to understand their relevance to social management within the community. The findings indicate that Sompa Tanah functions as a legal mechanism that not only regulates rights and obligations in marriage but also provides legal certainty within the marital bond. The legal security afforded to women serves as a safeguard for their rights as wives and mothers within a patriarchal society. As a legal mechanism, Sompa Tanah ensures social order and gains customary and cultural legitimacy, which strengthens the position of women in the Bugis social structure. Additionally, marriage, as a social bond, carries the risk of divorce, which is also legally acknowledged. Consequently, this paper recommends further comparative studies to explore the practice of Sompa Tanah across different regions to gain more comprehensive and in-depth knowledge.